THE EFFECT OF TAXPAYERS’ ATTITUDES, SUBJECTIVE NORMS AND PERCEIVED BEHAVIORAL CONTROL ON INDIVIDUAL TAX COMPLIANCE MODERATED BY RELIGIOSITY IN SURABAYA - Alimbudiono, Dr. Ria Sandra; Jie, Mellyana (UTSAHA: Journal of Entrepreneurship, 2024)
Religiosity has become specifically important for thoughts, cultures and societies. One of the non-economic factors that is often omitted by researchers is religiosity, that is, the religiosity values held by individuals that can effectively prevent negative attitudes and encourage positive attitudes of individuals. This research is concerned with the effect of attitudes, subjective norms and behavioral control perceived by taxpayers on personal tax compliance moderated by religiosity in Surabaya. This research took a sample for 200 respondents using purposive sampling technique. Data were collected using questionnaires and analyzed using descriptive statistics. This research represented that religiosity is a moderating variable that affects tax compliance when provided independent variables such as attitude, subjective norms and behavioral control. However, when religiosity is not provided as a moderating variable, perceived behavioral control does not affect tax compliance, while attitudes and subjective norms still affect tax compliance. This research also recommends to incorporate religious aspects when it comes to high tax compliance.